Bovine leukemia virus becomes established in dairy herds before the first lactation - Merlini, Ramiro; Gutierrez, Gerónimo; Alvarez, Irene; Jaworski, Juan Pablo; Carignano, Hugo Adrian; Poli, Mario Andres; Willems, Luc; Trono, Karina Gabriela (2017)
In this work, we studied seven groups of pregnant heifers from a consortium of dairy farms heavily infected with bovine leukemia virus (BLV). ELISA testing showed that the seroprevalence ranges of BLV in heifers between 36.1 and 66.5 %. No significant differences in proviral load were found when comparing heifers with adult cattle. Before their first delivery, more than 9.8 % of heifers show a high proviral load. Because BLV infection can occur during the first two years of life, the rationale of any strategy should be to take action as early as possible after birth.